(untitled) - Abdülkadir Çakır (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
This article deals with a long discussed issue, translation methods, their application to different types of texts and the factors that affect the choice of the appropriate translation method which is of extremely importance as it determines the quality of translation to a large extent. A translator who is furnished with the necessary information about the writer’s intention, the source text and the readership will be in a better position to do his job properly. A translator should start to do his task analyzing the source text he is going to translate considering all linguistic and cultural aspects along with the content, style and their equivalents in the target language. The effect created on the readers of the original text by the writer can be created on the reader of the translation by the translator if he takes the above mentioned factors into account